Integrated impact assessment of anthropogenic degradation in livestock agroecosystems of the Arid Chaco (Argentina) (Revista Ciencia Agraria, 2023)
Objectives: to develop and apply a procedure of integrated assessment for the impact of anthropogenic degradation using a composite indicator and to know the magnitude of the impact in three livestock agroecosystems. Methodology: a multiple case study design integrating mixed methods was applied. Used simple calculation and standardization methods to construct the composite indicator. For the collection of information on human variables, the sample was through networks and evaluated; the data collection unit, the social actors involved in each case; and the collection of information was carried out through semi-structured and structured interviews. For the biological-physical variables, the sample was the transect; the data universe, the farm; and the collection of information was carried out through systematic observational sampling. Results: moderate impact with risk of critical degradation was obtained for two of the farms, indicating the need to modify the management plan to avoid irreversible changes. The other showed critical impact with risk of severe impact, indicating the stoppage of activities and their intervention, to prevent the advancement of irreversible changes and allow rehabilitation. Conclusions: built indicator allowed carried out an integrated assess of the impacts and risks of occurrence of anthropogenic degradation. Simplicity of the methods used promotes its open public use. Applied procedure promotes a better understanding of the behavior of the studied phenomenon, greater effectiveness of management plans, and the viability and conservation of agroecosystems in arid zones, the most vulnerable to action of anthropogenic degradation.
Keywords: agroecosystems; anthropogenic degradation; composite indicator; impact; integrated assessment